2014
DOI: 10.1186/1752-2897-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal injuries in a major Scandinavian trauma center – performance assessment over an 8 year period

Abstract: IntroductionDamage control surgery and damage control resuscitation have reduced mortality in patients with severe abdominal injuries. The shift towards non-operative management in haemodynamically stable patients suffering blunt abdominal trauma has further contributed to the improved results. However, in many countries, low volume of trauma cases and limited exposure to trauma laparotomies constitute a threat to trauma competence. The aim of this study was to evaluate the institutional patient volume and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Although the incidence of unnecessary laparotomies has decrease due to improvements in imaging, they are still present in trauma centres, with 3.6% negative laparotomies, more frequent in stab injuries, and 6-27% nontherapeutic laparotomies, with complication rates up to 14.5% and 12% respectively. For BAT, the incidence of non-therapeutic laparotomies in Europe reaches 27% (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of unnecessary laparotomies has decrease due to improvements in imaging, they are still present in trauma centres, with 3.6% negative laparotomies, more frequent in stab injuries, and 6-27% nontherapeutic laparotomies, with complication rates up to 14.5% and 12% respectively. For BAT, the incidence of non-therapeutic laparotomies in Europe reaches 27% (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, it is suggested that the exposure of most European surgeons to an emergency laparotomy in severely injured patients is declining [1]. Penetrating injuries are a frequent indication for laparotomy in trauma patients [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most blunt trauma patients can nowadays be managed by non-operative management (NOM) [1,4,5]. This is in contrast to countries such as the USA and South Africa where exposure is higher due to high-volume presentation of trauma patients with penetrating abdominal injuries [1,3,6,7]. The current challenge is to provide an adequate level of care with satisfactory outcome for trauma patients who require an emergency laparotomy in Europe [8].…”
Section: Introductionmentioning
confidence: 99%
“…Penetrating injury is infrequent in most western European countries, whereas higher rates are seen in the US and South Africa [26,27]. In the Northern European countries, penetrating trauma is seen in 5-14% [28][29][30][31][32], and 37-58% [29,33,34] for patients undergoing trauma laparotomy, with gunshots accounting for 5-36% [28,[35][36][37][38]. In our study, penetrating trauma accounted for 16,6% of the trauma population and 66.3% for patients undergoing laparotomy.…”
Section: Discussionmentioning
confidence: 56%